The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/cmdc.201300541
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Growth‐Hormone‐Conjugated Nanodiamond Complex for Cancer Therapy

Abstract: It is highly desirable to develop a therapeutic, observable nanoparticle complex for specific targeting in cancer therapy. Growth hormone (GH) and its antagonists have been explored as cancer cell-targeting molecules for both imaging and therapeutic applications. In this study, a low toxicity, biocompatible, therapeutic, and observable GH-nanoparticle complex for specifically targeting growth hormone receptor (GHR) in cancer cells was synthesized by conjugating GH with green fluorescence protein and carboxylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…51 Similarly, Chu et al developed a nanodiamond complex with conjugation of recombinant growth hormone for protein-targeting of the surface membrane of A549 NSCLC cells. 65 Salaam et al developed a nanodiamond mediated drug delivery system to increase the specificity of doxorubicin by nanodiamond conjugation with doxorubicin and the DGEA peptide to target the α 2 β 1 integrins overexpressed in metastatic prostate cancers. 66 However, employing this strategy of nanodiamond conjugation for FND-mediated immunotherapy delivery has not yet been fully developed.…”
Section: Discussionmentioning
confidence: 99%
“…51 Similarly, Chu et al developed a nanodiamond complex with conjugation of recombinant growth hormone for protein-targeting of the surface membrane of A549 NSCLC cells. 65 Salaam et al developed a nanodiamond mediated drug delivery system to increase the specificity of doxorubicin by nanodiamond conjugation with doxorubicin and the DGEA peptide to target the α 2 β 1 integrins overexpressed in metastatic prostate cancers. 66 However, employing this strategy of nanodiamond conjugation for FND-mediated immunotherapy delivery has not yet been fully developed.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, GH-conjugated to a carboxylated nanodimond has been used to induce cell death in a non-small-cell lung cancer cell line (Chu et al, 2014) and this laser-mediated cancer-targeting platform may be widely used in the future. Pegvisomant, a specific GHR antagonist, has also been proposed as treatment for selected types of cancer (Kopchick et al, 2014).…”
Section: Extrapituitary Growth Hormone: Pathophysiological Rolesmentioning
confidence: 99%
“…In this study, its utility for screening malignant cancer was close to the results of Li et al, which enrolled 155 colorectal cancer and found notable differences with the comparison in the serum concentrations of 66 non-cancer diseases, representing the diagnostic value of 0.881 for discrimination. (18) Several researches also had reported the usefulness of materials therein CETM (19), (20), PTM(21), CTM, ETM (22) and HTM (23), (24) in lung cancer differential diagnosis, therapy monitoring and prognostics (25), (26). Age, gender, and smoking history had been found seldom effect for research population.…”
Section: Discussionmentioning
confidence: 99%